Christian Origins and the New Testament in the Greco-Roman Context Essays in Honor of Dennis R. MacDonald - Froelich, Margaret; Kochenash, Michael (Claremont Studies in New Testament and Christian Origins, 2016)
An exploration of the Christian origins in light of Greco-Roman literary practices